Lambing Frequency in the Ile de France, Suffolk and Babolna TETRA Stocks of Babolna c.o., Szendrő - Harcsa, Attila; Pál, Gábor; Komlósi, István; Jávor, András (Acta Agraria Debreceniensis, 2004)
Lambing frequency of three different genotypes was evaluated in the breeding stock of Babolna c.o. Szendrő. Ile de France, Suffolk and Babolna TETRA breeding ewes gave the data for the further evaluation. The main aim of this research was to find out if there is any significant effect of selected parameters (registration class, lambing season, lambing type and the years) on the lambing frequency, the period between consecutive lambings. Production parameters of 9,471 Ile de France, 1,244 Suffolk and 7,618 Babolna TETRA ewes were collected and processed. The analysis covered the period between the years 1989-1999. It was concluded that not all of the evaluated parameters had a significant effect on lambing frequency. Not all of the genotypes showed significant differences, according to the examined parameters.